PENGARUH KONTRIBUSI PENDAPATAN ASLI DAERAH DAN DANA TRANSFER TERHADAP KEMANDIRIAN FISKAL PEMERINTAH DAERAH DI PROVINSI BENGKULU - Khairani, Amelia; Mustika, Nelda (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aims to examine the effect of Regional Original Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Revenue Sharing Fund (DBH) on regional financial independence. This research employed a quantitative approach using panel data regression analysis through the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM), with model selection conducted using the Chow, Hausman, and Lagrange Multiplier tests. The results indicate that PAD has a positive and significant effect on regional financial independence, suggesting that higher local revenue enhances the ability of regional governments to finance development independently. In contrast, DAU, DAK, and DBH have negative and significant effects on regional financial independence, indicating that greater dependence on central government transfer funds tends to reduce regional fiscal autonomy. Therefore, optimizing local revenue sources is essential to strengthen regional financial independence and reduce dependency on intergovernmental transfers.